Factors associated with cardiovascular disease in patients with type 2 diabetes mellitus - Tan, Mun Chieng (2013)
Cardiovascular disease (CVD) is the leading cause of death in patients with type 2 diabetes mellitus (T2DM). Although patients with T2DM and CVD share common risk factors, the link between these diseases remains largely unexplained. Thus, this study aims to identify the determinants of CVD in T2DM patients. This study involved 313 patients aged 30 to 78 diagnosed with T2DM at two Malaysian government hospitals. Systematic random sampling method was applied in patient selection. Socio-demographic data was assessed using a pre-tested interviewer-administered structured questionnaire. Anthropometric measurements were performed according to standard procedures. Clinical and laboratory characteristics on cardiovascular risk factors [medical history, treatments, blood pressure, fasting plasma glucose, glycated haemoglobin (HbA1C), and lipid profile] were collected from patients' medical records, clinical examination and face-to-face interview. Dietary assessment (by means of a 24 h dietary recall), physical activity level [via International Physical Activity Questionnaire (IPAQ)], smoking and alcohol consumption habits were ascertained. A positive response rate of 100% was achieved. The mean age of study subjects was 55.7±9.2 years, with a mean duration of diabetes of 10.1±8.1 years; 52.1% subjects were females; and majority were Malays (47.0%). Approximately one third (36.1%, n=113) of the subjects were suffering from CVD. High prevalence of established coronary artery disease (30.7%), cerebrovascular disease (10.2%) and peripheral vascular disease (5.1%) were identified. There are significant relationships between CVD and non-CVD patients in the age, DM duration, gender, ethnicity, education, employment, personal and household monthly income, WHR, HDL-C level, triglycerides, hypertension, dyslipidaemia, nutrient intakes (calories, carbohydrate, protein, and total fat), physical activity level, smoking status and alcohol consumption as indicated by bivariate analysis (p<0.05). Binary logistic regression using forward stepwise method showed age (B=0.056, adjusted OR95% CI = 1.058 [1.018-1.099]; p=0.004), lower HDL-C level (B=-1.466, adjusted OR95% CI = 0.231 [0.087-0.613]; p=0.003), working status of self-employed (B=1.381, adjusted OR95% CI = 3.978 [1.626-9.733]; p=0.002), high (B=-1.114, adjusted OR95% CI = 0.328 [0.172-0.626]; p=0.001) compared to low physical activity level were significantly associated with higher CVD risk, upon adjustment for potential covariates. In conclusion, increased age, lower HDL-C, low physical activity level, and working status appeared to be related with CVD among the T2DM patients studied. Therefore, the importance of secondary and tertiary preventions to minimise the potential deterioration of metabolic control and quality of life accompanied CVD coexisted T2DM should be highly emphasized.